Feasibility of MRI-guided transurethral ultrasound for lesion-targeted ablation of prostate cancer - Anttinen M; Mäkelä P; Suomi V; Kiviniemi A; Saunavaara J; Sainio T; Horte A; Eklund L; Taimen P; Sequeiros RB; Boström PJ (My University, 2022)
Background: MRI-guided transurethral ultrasound ablation (TULSA) has been evaluated for organ-confined prostate cancer (PCa). The purpose of this study was to assess the safety and toxicity, accuracy and short-term evolution of cell-death after lesion-targeted TULSA.
Methods: This prospective, registered, Phase-I treat-and-3-week-resect-study enrolled six patients with MRI-visible-biopsy-concordant PCa. Lesions were targeted using TULSA with radical intent, except near neurovascular bundles (NVB). Robot-assisted-laparoscopic-prostatectomy (RALP) was performed at 3 weeks. Post-TULSA assessments included MRI (1 and 3 weeks), adverse events and quality-of-life (QoL) to 3 weeks, followed by RALP and whole-mount-histology. Treatment accuracy and demarcation of thermal injury were assessed using MRI and histology.
Results: Six patients (median age = 70 years, prostate volume = 60 ml, PSA = 8.9 ng/ml) with eight biopsy-confirmed MRI-lesions (PIRADS ≥3) were TULSA-treated without complications (median sonication and MRI-times of 17 and 117 min). Foley-catheter removal was uneventful at 2–3 days. Compared to baseline, no differences in QoL were noted at 3 weeks. During follow-up, MRI-derived non-perfused-volume covered ablated targets and increased 36% by 3 weeks, correlating with necrosis-area on histology. Mean histological demarcation between complete necrosis and outer-limit-of-thermal-injury was 1.7 ± 0.4 mm. Coagulation necrosis extended to capsule except near NVB, where 3 mm safety-margins were applied. RALPs were uncomplicated and histopathology showed no viable cancer within the ablated tumor-containing target.
Conclusions: Lesion-targeted TULSA demonstrates accurate and safe ablation of PCa. A significant increase of post-TULSA non-perfused-volume was observed during 3 weeks follow-up concordant with necrosis on histology. TULSA achieved coagulation necrosis of all targeted tissues. A limitation of this treat-and-resect-study-design was conservative treatment near NVB in patients scheduled for RALP.